MENULIS NARATIF DENGAN MENJARAKI-DIRI TERHADAP PENURUNAN GEJALA DEPRESI : Single Subject Case Design - Setiawati Intan Savitri; Bagus Takwin; Indri Romdonah (Universitas Andalas, 2019)
This research wants to find out whether there is a significant effect of writing techniques using own-name, as an intervention to reduce the level of depression. Subjects were young adults with moderate depression. Two interventions were carried out namely expressive writing and narrative self-distancing. The total of participants were 5, 2 participated in expressive writing interventions and 3 others participated in self-distancing narrative writing interventions. A single case-design experimental method and quantitative content analysis are used. The intervention process uses A-B-A design, where there are 3 phases, namely pre-intervention, intervention and follow-up which is carried out for 3 consecutive weeks. BDI-II as a baseline to measure the level of participant depression with a score between 0 - 63. The results showed that the level of participant depression measured by BDI-II from 3 participants who wrote narratives with self-distancing continued to decrease, 2 participants who wrote expressive writing showed inconsistent BDI-II results. The results of inter-rater validation using Cohen’s Kappa are at 0.759 - 0.844 which means very good. Content analysis shows that self-distancing narrative writing was relatively less in depressive sentences compared to participants in the expressive writing group.